IDENTIFIKASI RHODAMIN B PADA JAJANAN SEKOLAH DI KOTA BANDA ACEH - Ayu Nirmala Sari; Triya Elliyatri; Fazri Ardian Syah; Farisa Sabila; Reni silvia Nasution (KENANGA : Journal of Biological Sciences and Applied Biology, 2023)
Snacks in the environment around the school freely are a problem that is very risky for biological pollution such as the occurrence of worms due to the presence of bacteria in food which disturbs health a lot. This research was conducted to find out how many snacks containing Rhodamine B are in the lives of elementary school children. Based on the results of the study it was found that only 5 samples showed dark red and purplish colors so that out of 20 samples there were only 5 positive rhodamine B and 15 negative rhodamine B